Quantitative fluorescence resonance energy transfer-based immunoassay for activated complement C1s - Ye, Jun; Xu, Jie; Zhang, Chuanmeng; Zhu, Li; Xia, Sheng (Frontiers in Immunology, 2023)
Objectives: C1s activation is associated with the pathogenesis of various diseases, indicating the potential value of C1s activation detection in clinic. Here we aimed to establish fluorescence resonance energy transfer (FRET)-based immunoassay for the quantitative detection of activated C1s in serum. Methods: FRET-based fluorogenic peptides, sensitive to the enzymatic activity of activated C1s, were prepared and labeled with the fluorophore ortho-aminobenzoic acid (Abz) and quencher 2,4-dinitrophenyl (Dnp), and then were further selected depending on its Kcat/Km value. C1s in the samples was captured and separated using anti-C1s-conjugated magnetic microbeads. Next, enzymatic activity of activated C1s in samples and standards was examined using fluorescent quenched substrate assays. Limit of detection (LOD), accuracy, precision, and specificity of FRET-based immunoassay were also investigated. Results: This method presented a linear quantification range for the enzymatic activity of activated C1s up to 10 μmol min-1 mL-1 and LOD of 0.096 μmol·min-1·mL-1 for serum samples. The recovery of the method was in the range of 90% ~ 110%. All CV values of the intra-analysis and inter-analysis of three levels in samples were less than 10%. The cross-reaction rates with C1r enzyme, MASP1, and MASP2 were less than 0.5%. No significant interferences were found with bilirubin (0.2 mg mL-1), Chyle (2000 FTU), and haemoglobin (5 mg mL-1), but anticoagulants (EDTA, citrate and heparin) inhibited the enzymatic ability of activated C1s. Thus, this established method can be used for the determination of active C1s in human serum samples in the concentration interval of 0.096-10.000 μmol min-1 mL-1. Conclusions: One anti-C1s-based FRET immunoassay for activated C1s detection in serum samples were established, and it will be useful to explore the role of C1s activation in the pathogenesis, diagnosis and treatment in complement-related diseases.